PEMBELAJARAN BAHASA ARAB SEBAGAI DASAR PENGEMBANGAN KETERAMPILAN MEMBACA KITAB - Asmuki Asmuki; Ahmadi Muhammadiyah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
Arabic in its implications in the world of Islamic religious education, especially in Islamic sciences, has a urgent role. As the language of instruction for various references in the rapidly developing branches of science in the global era, Arabic cannot be excluded, although its existence does not exceed English as the language of international communication. It is to enter the doors of Islamic knowledge that Arabic is an important and to be important role to be learned from various branches of linguistics. Both grammatical and various Arabic language skills. For this reason, in every Madrasah, pesantren, and some schools, Arabic language is required to be included in their curriculum.